The Role of the Family in Supporting the Enhancement of Early Childhood Social Competence at RA Subulussalam Juntikedokan Kabupaten Indramayu - Nursamsy, Dede (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2025)
Background: Family involvement is critical in early childhood social competence development, particularly in Islamic early childhood education where moral, spiritual, and social learning are integrated. However, empirical studies examining family support for social competence within Islamic educational contexts in Indonesia remain limited.Objective: This study examines how families support early childhood social competence enhancement at RA Subulussalam Juntikedokan, Indramayu Regency, identifying family support mechanisms, barriers and facilitators of engagement, and the influence of Islamic pedagogical values on family involvement.Method: Applying qualitative design, data were collected from 12 parents, 6 teachers, and 3 administrators through semi-structured interviews, focus group discussions, classroom observations, and document analysis. Thematic analysis identified patterns related to family support practices, communication structures, and value-based engagement.Findings and Implications: Three primary support mechanisms emerged: parental understanding integrating Islamic values into social competence conceptualization, intentional home-based practices emphasizing emotional and social learning, and structured family–school communication facilitating child-centered collaboration. Islamic pedagogical values significantly shaped engagement, with parents perceiving social competence as moral-spiritual development rather than merely behavioral skill acquisition. Barriers included time constraints, limited parental knowledge, and socioeconomic pressures, though strong institutional commitment sustained engagement. These findings extend international literature by demonstrating that culturally and religiously informed frameworks enhance participation despite structural constraints.Conclusion: Authentic family–school partnerships are foundational for optimizing early childhood social competence within cultural and spiritual frameworks. Integrating Islamic values into family engagement strengthens children's emotional, moral, and social development, underscoring the need for contextually grounded involvement models in Islamic early childhood education.